Improving The Quality of Education in Preschool Educational Organizations (Eurasian Journal of Learning and Academic Teaching, 2022)
Pedagogical games in preschool organizations are characterized by the style of play as follows: by topic; photo; business, imitation, dramatic games. All pedagogical games used in the system of higher, secondary special, vocational education are, in essence, business games. Because they are usually developed within a specific learning discipline: there are roles and plots, different situations are imitated. That is, business games used in the system of higher and secondary special vocational education include all components of pedagogical games